Line Spread Test Results for Commercially Available the White Rice Porridge with Salmon - Including the Effect of Four Types of Thickening Agents Added after Blending - (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: commercial product; white rice porridge with salmon; lin spread test (LST); thickener